Social Entrepreneurship in Non-Profit and Profit Sectors : Theoretical and Empirical Perspectives - Peris-Ortiz, Marta; Teulon, Frédèric; Bonet-Fernandez, Dominique (Springer International Publishing : Imprint : Springer, 2017)
This volume examines the theoretical and empirical landscape of social entrepreneurship in both non-profit and profit sectors. It extends the traditional view of social entrepreneurship to include the environmental and institutional factors that affect the emergence of social entrepreneurship activities, such as formal laws, regulations, procedures and informal institutions. The editors aim to provide evidence and increased understanding of this growing phenomenon. Social Entrepreneurship is gaining recognition as a key element of economic and social development. It embraces a wide set of situations with a broad scope of activities in for-profit and non-profit organizations interested in social performance and/or in economically profitable performance, with an emphasis on achieving social aim. In the strict sense, social entrepreneurship corresponds to entrepreneurs whose main concern is to achieve social objectives rather than to obtain personal financial profits. However, there is still much to be learned about the dynamics and processes of social entrepreneurship. The current literature in the field has tended to focus on psychological experiences and personal characteristics, or on organizational perspectives such as resources, capabilities and leadership. This book intends to provide theoretical frameworks and empirical studies to this very new and broad field. Specifically, this book provides a collection of contemporary research in the following topics: How to create opportunity through social innovation How to detect entrepreneurial opportunity to meet social needs How to develop social entrepreneurship, while still seeking profits How to discover opportunities for different forms of social entrepreneurship Featuring contributions from around the world, this book is a valuable source for students, academics, researchers, policy makers, and professionals in the area of social entrepreneurship.
Keywords: Business.; Small business.; New business enterprises.; elektronické knihy; electronic books